2012
DOI: 10.4049/jimmunol.1101877
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TNF-α to Neoangiogenic Vessels Enhances Lymphocyte Infiltration in Tumors and Increases the Therapeutic Potential of Immunotherapy

Abstract: Abnormal tumor vasculature impairs T lymphocyte adhesion to endothelial cells and lymphocyte extravasation into neoplastic tissues, limiting the therapeutic potential of both active and adoptive immunotherapies. We have found that treatment of tumor-bearing mice with NGR-TNF, a Cys-Asn-Gly-Arg-Cys peptide-TNF fusion product capable of altering the endothelial barrier function and improving drug penetration in tumors, associated with the intratumor upregulation of leukocyte-endothelial cell adhesion molecules, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 44 publications
6
116
0
Order By: Relevance
“…In support of this hypothesis, we found that TRAMP mice receiving a DLI from a male-sensitized female donor experienced accelerated CD3 þ cell infiltration of the prostatic tissue (unpublished data). Thus, it is likely that the use of primed T cells, or of other strategies favoring tumor infiltration (36) and/or tumor antigen cross-presentation, might mimic the effect of tumor-directed vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, we found that TRAMP mice receiving a DLI from a male-sensitized female donor experienced accelerated CD3 þ cell infiltration of the prostatic tissue (unpublished data). Thus, it is likely that the use of primed T cells, or of other strategies favoring tumor infiltration (36) and/or tumor antigen cross-presentation, might mimic the effect of tumor-directed vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, targeting TNF to neoangiogenic vasculature, induces upregulation of ICAM-1/VCAM-2 leukocyte adhesion molecules on endothelial cells, and release of proinflammatory cytokines and chemokines in the tumor microenvironment. Remarkably, these modifications favor a rapid and long lasting infiltration of tumor-specific CD8 C T cells 11 Similarly, tumor infiltration by CD8 C T cells, was induced by an RGR-targeted TNF (i.e. TNF-RGR administered at doses in the microgram range).…”
mentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-α is an inflammatory cytokine frequently present in the tumor microenvironment. TNF-α is primarily secreted by tumor-associated macrophages and it initiates chronic inflammation (2). TNF-α has biphasic effects, by which it induces tumor cell apoptosis at high doses while it accelerates tumor invasion and metastasis with long-term administration of low doses (3).…”
Section: Introductionmentioning
confidence: 99%